Technology-supported environments for learning through cognitive conflict - Anne McDougall (Association for Learning Technology, 2002)
This paper examines ways in which the idea of cognitive conflict is used to facilitate learning, looking at the design and use of learning environments for this purpose. Drawing on previous work in science education and educational computing, three approaches to the design of learning environments utilizing cognitive conflict are introduced. These approaches are described as confrontational, guiding and explanatory, based on the level of the designer's concern with learners' pre-existing understanding, the extent of modification to the learner's conceptual structures intended by the designer, and the directness of steering the learner to the desired understanding. The examples used to illustrate the three approaches are taken from science education, specifically software for learning about Newtonian physics; it is contended however that the argument of the paper applies more broadly, to learning environments for many curriculum areas for school levels and in higher education.